Genetic diversity of coding sequence (CDS) region of HSP70 gene in Bali cattle - Bonawati, Y. G. M.; Suhendro, I.; Jakaria, J.; Noor, R. R. (Diponegoro University, 2025)
This study aimed to investigate the genetic diversity of the Heat Shock Protein 70 (HSP70) gene in the coding sequence (CDS) region and its association with physiological responses in Bali cattle. The samples used in this study consisted of 62 Bali cattle from two different locations in Bali and Se-rading. Physiological data, including respiratory rate, heart rate, rectal temperature, and heat tolerance coefficient (HTC), were collected. The HSP70 gene was amplified using two pairs of primers to target the coding region. SNPs of the HSP70 gene were identified through sequencing. The diversity of SNPs in the coding sequence of the HSP70 gene was determined using the FinchTV 1.4.0 application and version X of the Molecular Evolutionary Genetic Analysis (MEGA) program. In contrast, the association of HSP70 gene SNPs with physiological responses in Bali cattle was evaluated using the GLM method in IBM SPSS Statistics 26. The research discovered nine SNPs within the CDS region of the HSP70 gene, comprising eight synonymous SNPs (c.24C>T, c.31C>T, c.117C>A, c.126G>A, c.324G>A, c.333C>T, c.573G>C, c.1074C>T) and one nonsynonymous SNP (c.1265C>T), which caused an amino acid substitution from threonine (T) to methionine (M). The SNP diversity in the coding sequence of the HSP70 gene showed no significant association (P > 0.05) with physiological responses, including respiratory rate, heart rate, rectal temperature, and heat tolerance coefficient (HTC). The SNPs discovered in the coding region of the HSP70 gene exhibited polymorphism in Bali cattle.